2020
DOI: 10.21203/rs.3.rs-18318/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of probiotics and Bidens pilosa on the performance and gut health of chicken during induced E. tenella infection

Abstract: Background Probiotics and Medicinal plants are widely used as an alternative to treat different kinds of the acute and chronic diseases in all over the world. Bidens pilosa is commonly used as foods and therapeutics against various pathogens including protozoan. In the present study probiotics and Bidens pilosa were used to explore the anticoccidial activity during experimental infection of Eimeria tenella ( E. tenella ) in chicken Methods One hundred and fifty one-day-old Chinese yellow breed chickens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Both B. pilosa and A. indica have been reported to possess anti-protozoan activity 8 , 9 . We also reported that B. pilosa had anti-coccidial activity in chickens, as published previously 4 , 12 . B. pilosa consistently intervened with the Eimeria life cycle at the stage of oocyst sporulation and sporozoite invasion 12 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both B. pilosa and A. indica have been reported to possess anti-protozoan activity 8 , 9 . We also reported that B. pilosa had anti-coccidial activity in chickens, as published previously 4 , 12 . B. pilosa consistently intervened with the Eimeria life cycle at the stage of oocyst sporulation and sporozoite invasion 12 .…”
Section: Discussionsupporting
confidence: 88%
“…Chickens infected with Eimeria often develop sick bird syndrome, including bloody stools, gut lesions, oocyst excretion, loss of BWG, reduced egg production, poor FCR, and high mortality. It was estimated that the global cost of coccidiosis in chickens was around 6 billion US dollars in 2016 4 . Although anti-coccidial drugs have been routinely used in the poultry industry for the past 80 years 5 , antibiotic-free approaches to control coccidiosis are in great demand.…”
Section: Introductionmentioning
confidence: 99%